Combining multiple biomarkers differentiates between active SJIA, SJIA‐MAS and EBV‐HLH - Weaver, L. K. (Clin Exp Immunol, 2017)
Cytokine storm syndromes are a clinically heterogeneous group of conditions resulting from a maladaptive host response to an inflammatory trigger. These syndromes lead to rapid progression of immune‐mediated damage to healthy tissues resulting in life‐threatening multi‐system organ failure. Prompt recognition of disease and medical intervention to limit damage to healthy tissues is essential to prevent cytokine storm morbidity and mortality. However, the diagnosis of cytokine storm syndromes is challenging, given the clinical heterogeneity in disease presentations. Therefore, expeditious and readily available tests to diagnose disease and differentiate between the various types of cytokine storm syndromes are of clinical utility. The recently published work of Shimizu and colleagues brings us closer to making this a reality.